Serum Calcium and Phosphate in Children with Autism Spectrum Disorder - Afroz, Sharmin; Siddiqi, Umme Raihan; Mahruba, Nusrat; Shahjadi, Shorifa; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2020)
Background:Autism spectrum disorder (ASD) is a complex disorder of neuronal development which may cause lifelong disability. The etiology of ASD involves gene-environmental interaction. Calcium signal is crucial for neuronal communication and neuro-plasticity and phosphate is related to neural energy metabolism. Therefore, deficiency of these minerals may act as an environmental risk factor for the development of ASD. Objective: To assess serum calcium and phosphate in children with ASD. Methods: This cross-sectional comparative study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University(BSMMU) Dhaka from March 2018 to February 2019. For this, 50 ASD children of both sex (age 3 to10 years) diagnosed by pediatric neurologist were included as ‘Study’ participants through ‘Parents Forum of differently abled children, Mohakhali, Dhaka’ and for comparison, age, BMI and sex matched 50 apparently healthy children were enrolled, as ‘Control’. Serum calcium and phosphate level of all children were estimated by colorimetric method. All data were expressed as mean±SD, range and percentage. For statistical analysis, Chi- Square test, Shapiro Wilk test and independent sample ‘t’ test was done, as applicable. Results:The mean serum calcium was significantly (p<0.01) lower in ASD children compared to control, though the mean values were within normal reference range in both groups. However, hypophosphatemia was found in 4% of ASD children. Conclusion:From this study, it may be concluded that ASD children was associated with lower serum calcium level and hypophosphatemia.Therefore, adequate dietary intake of calcium and phosphate is recommended for children with ASD. J Bangladesh Soc Physiol. 2020, December; 15(2): 72-77